The discourse of a ‘smart’ technology: implications for educational practice - Crook, Charles (Inderscience, 2016)
The term ‘smart’ has become widely and sometimes carelessly employed in relation to contemporary design. However, in certain areas of cultural practice it also has acquired a more specialised and focussed meaning. One such area is education. The present paper explores the discourse of smart as it is emerging in relation to both educational technologies and educational spaces. The characteristics of smart learning tools and smart sites for learning with such tools are defined in terms of their capability for organising regulative interactions. However, it is argued that these artefacts and these spaces cannot be fully productive unless they are enveloped by a framework of human intelligence and judgement. This locates the teacher has having an important, novel, and distinctive role in the management of smart education. The range of such responsibilities is illustrated and related to contemporary themes in the psychology of learning